Faktor-faktor peminjaman bahasa asing ke dalam bahasa Arab: satu kajian linguistik sejarawi - Hassan Azhari, Abd Rauf (Universiti Putra Malaysia Press, 2006)
This linguistic study investigates the incorporation of loan words into Arabic and discusses in detail those factors that influence such incorporation. Among the main influencing factors that were previously mentioned by Arabic language and linguistics scholars are trading, political, social and religious factor. The six major factors contributed to the occupation of foreign words into Arabic language are discussed here. All these factors play direct and indirect roles in giving rise and existence to the use of foreign words into Arabic. The researcher believes that the most influential factor contributing to the existence of loan words into Arabic is the translation factor.